2000
DOI: 10.1523/jneurosci.20-24-09310.2000
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses in the Retinotopic Representation of the Blind Spot in the Macaque V1 to Stimuli for Perceptual Filling-In

Abstract: When visual stimuli that cover the entire blind spot are presented monocularly, the color and brightness of the surrounding field are seen within the blind spot, although it receives no retinal input. Important questions about such perceptual filling-in are whether neurons in the visual system representing visual field locations within the blind spot are activated when filling-in occurs and, if so, what the properties of these neurons are. To address these questions, we recorded the activities of single neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…The present finding, though limited to brain activity corresponding to color or brightness filling-in and illusory contours of an illusory transparent surface, is consistent with other findings that showed V1 activity for uniform surface and brightness (9,10,54) in the sense that roles of V1 neurons are not restricted to be a simple orientation filter of lines (8). V1 seems to play a greater variety of roles than was once thought.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present finding, though limited to brain activity corresponding to color or brightness filling-in and illusory contours of an illusory transparent surface, is consistent with other findings that showed V1 activity for uniform surface and brightness (9,10,54) in the sense that roles of V1 neurons are not restricted to be a simple orientation filter of lines (8). V1 seems to play a greater variety of roles than was once thought.…”
Section: Discussionsupporting
confidence: 92%
“…Although recent findings have shown that V1 in the monkey brain is activated for surface processing (9,10,40,41), it has been suggested that this activation results solely from feedback from higher cortical stages. However, when we controlled for attention, which could give feedback signals from the higher-order visual areas, significant fMRI activity was observed only in the part of V1 that retinotopically corresponds to a color filled-in area of an illusory transparent surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurophysiological studies of monkey and cat visual cortex provide some support for the filling-in hypothesis. A small proportion of neurons, responding to the interiors of achromatic surfaces, exhibit properties consistent with aspects of human brightness constancy (MacEvoy and Paradiso, 2001), brightness induction (Rossi et al, 1996;Rossi and Paradiso, 1999;Kinoshita and Komatsu, 2001;Peng and Van Essen, 2005), the Craik-Cornsweet-O'Brian brightness illusion (Hung et al, 2001; Roe et al, 2005), and surface completion of the retinal blind spot (Komatsu et al, 2000(Komatsu et al, , 2002. No neurophysiological study, however, has yet revealed evidence of a topographic cortical representation corresponding to uniform surface regions von der Heydt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%